A Just Peace Ethic Primer : Building Sustainable Peace and Breaking Cycles of Violence - McCarthy, Eli Sasaran (Georgetown University Press, 2020)
How can we build a more sustainable peace? Why do we so often get stuck in vicious cycles of violence even with good intentions? How do we become better at constructively engaging conflict? By reflecting on cases of contemporary issues and conflicts, Just Peace Ethic enables us to address these pressing questions and see more clearly the value of a just peace ethic. Eli McCarthy's edited book informs people about an emerging just peace ethic and deepens the imagination about how it might provide fruitful moral guidance for various types of situations, taking a case-based approach to exploring and teaching it. Although there are articulations of just peace approaches, there is still a lack of scholarship illustrating how such an approach might function with particular cases. McCarthy and contributors address this gap by providing essays that apply and refine a virtue-based just peace ethic in the context of particular cases, beginning with three chapters that each address a facet of just peace, written by known scholars. Case studies follow, addressing issues internationally, among them the death penalty, immigration, racism in the US, non-state terrorism, the conflicts in South Sudan, El Salvador, Kenya, the Democratic Republic of Congo, and The Philippines. This book has potential course adoption appeal, as it is designed for learning about the just peace ethic and is written approachably.